Analysis of Study-Life Balance Among Vocational Students for the Development of a Mental Health Promotion Platform - Dhyani Ayu Perwiraningrum; Iwan Abdi Suandana; Riskha Dora Candra Dewi; Rinda Nurul Karimah (International Journal of Healthcare and Information Technology, 2026)
Mental health challenges among vocational college students have increased alongside intensive academic workloads and practical training demands. Study–life balance has emerged as a critical concept for understanding these challenges, as it reflects students’ ability to manage academic responsibilities, personal needs, and psychological recovery. However, empirical evidence linking study–life balance with the conceptual development of digital mental health promotion platforms in the vocational education context remains limited. This study employed a quantitative descriptive cross-sectional design to examine study–life balance and mental health support needs among vocational students. Data were collected from 105 students using a questionnaire adapted from the Depression Anxiety Stress Scale (DASS-21), complemented by items assessing digital mental health application use and feature preferences. Stratified random sampling was applied to ensure representation across study programs and academic levels. The findings indicate high levels of academic stress, difficulties in maintaining study–life balance, and insufficient rest time among students, alongside strong interest in digital mental health platforms despite low prior usage. Preferred features included activity management, self-assessment tools, and access to professional support, providing an empirical foundation for future platform development.